High-efficiency composite sludge dewatering conditioner as well as preparation and use methods thereof

By using a composite sludge dewatering conditioner composed of polydimethyldiallyl ammonium chloride and a copolymer of polymerized iron sulfate, the problems of complexity, narrow application scope and secondary pollution of existing sludge dewatering agents are solved, and the sludge moisture content is reduced and the sludge increase is controlled, which is environmentally friendly, efficient and low-cost.

CN119591307AInactive Publication Date: 2025-03-11XIAN QINGZHIYUAN ENVIRONMENTAL PROTECTION TECHNOLOGY CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202510142533.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-10
Publication Date
2025-03-11
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing sludge dehydrating agents have problems such as complex injection of agents, narrow application scope, large injection volume, obvious capacity increase, high cost, serious equipment corrosion, and difficult-to-degrade substances to cause secondary pollution, which is difficult to effectively reduce the sludge moisture content and sludge increase.

Method used

A composite sludge dehydration conditioner consisting of polydimethyldiallyl ammonium chloride and polymeric iron sulfate, sodium peroxycarbonate particles and porous slag particles is used to promote the aggregation of sludge particles and moisture release through electrical neutralization, floc skeleton and advanced oxidation.

Benefits of technology

The sludge moisture content has been significantly reduced, the sludge increase is small, the cost is low, and the environmentally friendly. It is suitable for deep dehydration and conditioning of municipal sludge, river bottom sludge and industrial sludge, and there is no need for difficult degradation or toxic substances.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119591307A_ABST
    Figure CN119591307A_ABST
Patent Text Reader

Abstract

The invention provides an efficient composite sludge dewatering conditioner and a preparation and use method thereof, and belongs to the technical field of sludge treatment agents, the sludge dewatering conditioner comprises poly dimethyl diallyl ammonium chloride, a polyferric sulfate solution, sodium percarbonate particles and slag porous particles; the polymeric ferric sulfate solution is a liquid with the effective iron content of 6-16%; the poly dimethyl diallyl ammonium chloride and the polymeric ferric sulfate solution are subjected to a mixed reaction under the heating condition according to the weight ratio of 1: (12-20), and a copolymer of poly dimethyl diallyl ammonium chloride and polymeric ferric sulfate is obtained; a copolymer is generated through a mixing reaction, sodium percarbonate particles and slag porous particles are added while stirring is conducted, and a finished product is obtained after sufficient and uniform mixing is conducted. The sludge water content can be reduced, the sludge increment is small, the use method is simple and convenient, the volume and the amount of the sludge are greatly reduced, the cost is low, and the method is environment-friendly.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sludge treatment agents, and in particular to a high-efficiency composite sludge dehydration conditioning agent and a preparation and use method thereof. Background Art

[0002] The sludge from municipal sewage treatment plants is a viscous and easily corruptible substance produced during sewage treatment. It is mainly composed of various aerobic, anoxic and anaerobic microorganisms, and is also mixed with mud, sand, fiber, animal and plant residues and organic matter, metals, bacteria, eggs, colloids and other complex mixtures contained in the original sewage. The sludge discharged from the sewage treatment plant is generally a loose, colloid paste with a water content of 95%-99%. It has the physical and chemical characteristics of light specific gravity (less than or equal to 1g / cm3), large volume (tens of times the volume of the solid matter contained), strong thixotropy (not easy to dehydrate), and extremely easy to corrupt and smell, which is very unfavorable for treatment and transportation. The amount of municipal sludge produced is large and not increasing. If it is not properly handled and disposed of, it will pose a serious threat to the environment and human life. At present, the treatment and disposal of sludge has become a major technical problem faced by urban sewage treatment plants. Therefore, how to effectively dehydrate the sludge, reduce the moisture content of the sludge, greatly reduce the volume of the sludge, facilitate the smooth progress of the subsequent sludge stabilization treatment process and reduce the cost of sludge treatment, so as to achieve harmless and reduced sludge treatment has become a key problem in the sludge industry and an inevitable development trend.

[0003] The surface of sludge particles carries a large amount of negative charge. The particles repel each other due to electrostatic repulsion and exist stably. It is difficult for them to agglomerate to form larger particles. In addition, due to the high hydrophilicity of sludge, the large amount of water contained in the sludge is difficult to remove. Therefore, before the sludge is mechanically dehydrated, the sludge must be conditioned to make it easier for the sludge particles to agglomerate and form larger floc particles, and the large amount of water contained in the sludge is easier to remove. There are many ways to condition sludge, among which chemical conditioning is widely used because of its advantages such as simple operation and better sludge dehydration effect after conditioning.

[0004] The so-called chemical conditioning method is to add one or several sludge dehydrating agents to the sludge to condition the sludge, and change the properties of the sludge particles to make it easier to remove the water from the sludge. Commonly used sludge dehydrating agents include inorganic sludge dehydrating agents, organic polymer sludge dehydrating agents, organic-inorganic composite sludge dehydrating agents and biological sludge dehydrating agents. Among them, inorganic sludge dehydrating agents have the best dehydration effect. Taking "FeCl3+CaO" as an example, it can reduce the sludge moisture content to between 50% and 60% in combination with plate and frame filter press. However, this method requires a large amount of addition, high processing costs, and a sludge increase of up to 15~25%, which increases the subsequent sludge transportation and disposal costs. In addition, the use of acid and alkali reagents seriously corrodes the equipment, increasing the equipment operation and maintenance costs. The dosage of organic polymer sludge dehydrating agent is small, and the sludge increment is small. Cationic polyacrylamide (CPAM) is the most widely used organic polymer sludge dehydrating agent at present, but it can only reduce the sludge moisture content to between 65% and 75% when combined with plate and frame filter press. Moreover, CPAM is difficult to degrade under natural conditions. The acrylamide monomer produced by its degradation is a highly toxic substance with neurotoxicity, causing secondary pollution to the environment. Organic-inorganic composite dehydrating agents have strong complementarity in performance and cost. Therefore, the compounding of inorganic and organic polymer dehydrating agents has become an important direction of dehydrating agent research. The research and development of inorganic-organic polymer flocculation dehydrating agents is mostly still in the experimental stage, with few industrialized products, and there are problems such as single type, uncontrollable molecular structure, poor stability and poor solubility. Microbial sludge dewatering agent is a new type of high-efficiency, non-toxic conditioning agent with biodegradability and safety obtained by fermentation, extraction and purification from microorganisms or their secretions using biotechnology. It has the advantages of high flocculation activity, safe biodegradability and no secondary pollution, and is receiving more and more attention. In particular, activated sludge itself is rich in a large number of flocs, and this advantage can be used to extract and prepare microbial conditioning agents from activated sludge, and it has a good conditioning effect. However, it is still in the stage of strain screening and the research level is low. It may have great development in the future.

[0005] In recent years, researchers have developed a variety of deep sludge dehydration methods, such as microwave, acid-base, ultrasound, electrochemistry, and Fenton oxidation, but different treatment technologies are greatly affected by sludge characteristics, and the enhanced dehydration performance needs to be improved, and more new and efficient conditioning agents need to be developed. To this end, a lot of research has been done to develop efficient and environmentally friendly dehydration conditioning agents to improve the dehydration performance of sludge.

[0006] The publication number CN108083613A, "An efficient dehydrating agent for sewage sludge, its preparation method and application", discloses that chitosan is modified by graft copolymerization reaction, and chitosan is used as a graft skeleton to synthesize a sludge dehydrating agent with a larger molecular weight and a higher cation concentration, and the following components are reacted by weight to obtain chitosan 10-30 parts; cationic polyacrylamide 40-80 parts; dimethyl divinyl propyl ammonium chloride 10-30 parts; initiator 0.08-0.2 parts. Its disadvantage is that the introduction of cationic polyacrylamide, the free monomer is neurotoxic, and it is easy to cause secondary pollution.

[0007] The "New Sludge Dewatering Agent" with the publication number CN 108409104A discloses that a copolymer of dimethyldiallylammonium chloride and acrylamide is obtained by using dimethyldiallylammonium chloride and acrylamide as raw materials, potassium persulfate, sodium persulfate and ammonium persulfate in a mass ratio of 3:2:1 as initiators, and then adding aluminum salt, iron salt, quicklime, fly ash and other coagulants to prepare the copolymer. The disadvantage is that the composition is complex and acrylamide is toxic and easily causes secondary pollution.

[0008] The publication number CN 104649533A discloses a method for composite conditioning and deep dehydration of sludge. It discloses using zero-valent iron or nano zero-valent iron as an activator to react with potassium monopersulfate, peroxymonosulfate, peroxydisulfate and other persulfides to produce free radicals to destroy sludge extracellular polymers, and cooperates with industrial by-product gypsum to form conditioned sludge with a new skeleton morphology, improve the filtration performance of sludge, and reduce the sludge moisture content to below 60%. The disadvantages are that the composition is complex, the dosage is large, and an activator needs to be added to produce active free radicals. The dosage of gypsum is 10%-40% of the dry sludge, the sludge increment is large, and the process is cumbersome.

[0009] The "Method for Improving the Dewatering Performance of Municipal Sludge" with publication number CN 105502882 A discloses that the conditioning agent is composed of the following parts: 0.04-0.08 grams of Fe per gram of dry sludge 2+ , 0.10~0.20 g persulfate, 0.32~0.44 g ordinary Portland cement and 0.48~0.64 g quicklime. Its main advantage is high treatment efficiency, but its disadvantages are that the conditioning time is too long, the amount of conditioning agent is high, the cost is high, and the dewatered sludge is alkaline, which is not conducive to subsequent disposal.

[0010] The "composite conditioner for sludge dehydration and sludge dehydration method" with publication number CN 106746482 A discloses that the composite conditioner includes an organic coagulant (polydimethyldiallyl ammonium chloride or acrylamide copolymer, etc.), an inorganic coagulant (aluminum salt or iron salt) and an auxiliary agent (chitosan hydrochloride, sodium dodecylbenzene sulfonate or polyvinyl alcohol, etc.). The advantage of this composite conditioner is that it can adapt to a neutral pH and does not have a volume expansion problem, which does not affect the subsequent resource treatment and disposal of the mud cake. The disadvantage is that the composition of the sludge conditioner is complex and the economic benefit is low.

[0011] Although the above inventions have their own advantages and innovations, they still have the following shortcomings when applied to sludge deep dehydration: (1) The dosage of the reagent is complicated and its application range for sludge of different properties is narrow.

[0012] (2) The amount of conditioning agent added is large, the volume increase is obvious, the price is expensive, and the subsequent sludge transportation and disposal costs are increased.

[0013] (3) The conditioning agent has complex components, a long conditioning time, a cumbersome conditioning process, and high time and labor costs.

[0014] (4) Some processes require sludge to be treated by adjusting pH or heating, which consumes a lot of energy and can easily cause equipment corrosion.

[0015] (5) Some use CPAM, which is difficult to degrade. The free acrylamide monomer is neurotoxic and can easily cause secondary pollution.

[0016] (6) It is necessary to add catalysts, initiators, activators, etc., which is costly and produces large amounts of sludge.

[0017] Therefore, it is necessary to provide a high-efficiency composite sludge dewatering conditioner and a preparation and use method thereof to solve the problems existing in the above-mentioned prior art. Summary of the invention

[0018] In view of this, the present invention provides a high-efficiency composite sludge dewatering conditioner and a preparation and use method thereof, which can reduce the moisture content of sludge while increasing the sludge volume, is easy to use, significantly reduces the volume and amount of sludge, is low in cost and is environmentally friendly.

[0019] To achieve the above object, the present invention provides a high-efficiency composite sludge dehydration conditioner, comprising polydimethyldiallylammonium chloride, polyferric sulfate solution, sodium percarbonate particles and slag porous particles; The polyferric sulfate solution is a liquid having an effective iron content of 6 to 16%; The polydimethyldiallyl ammonium chloride and the polyferric sulfate solution are mixed and reacted in a weight ratio of 1:(12-20) under heating conditions to obtain a copolymer of polydimethyldiallyl ammonium chloride and polyferric sulfate.

[0020] The present invention promotes the formation of copolymers by adding polydimethyldiallylammonium chloride and polyferric sulfate, and controlling the effective iron content and the addition ratio, and more effectively exerts the respective advantages of polydimethyldiallylammonium chloride and polyferric sulfate, mainly reducing the surface charge of sludge colloidal ions through electrical neutrality, compressing the colloidal diffusion layer to destabilize the particles, and converting the surface attached water into free water, and at the same time, by virtue of the adhesion bridging, netting and sweeping effects of the polymer chain, the original tiny sludge particles are aggregated into larger particles, improving the sludge settling performance and the sludge dewatering performance. Compared with the monomers of the two, the formed copolymer has less usage, small sludge increment, and significant dehydration effect, and can make the sludge settle quickly.

[0021] Sodium percarbonate can produce hydrogen peroxide at room temperature, which reacts with iron in the copolymer to generate hydroxyl radicals (-OH). The two substances interact with each other to form strong oxidizing properties, oxidizing sludge and its extracellular enzymes, including macromolecular organic matter and cell structure. The cell walls of sludge microorganisms are destroyed, and macromolecular organic matter such as proteins and polysaccharides are degraded into small molecules, which is beneficial to dehydration, reducing the moisture content of sludge, and facilitating the release and outflow of water, thereby reducing the mechanical dehydration time. Slag porous particles are environmental multifunctional materials with low cost, huge specific surface area and large porosity, and good physical and chemical stability. They can be used as floc skeletons for sludge dehydration to maintain fluid channels, reduce the interfacial tension between solids and liquids, and release the water contained in the sludge floc grid, which is beneficial to the deep removal of water from the sludge.

[0022] The present invention directly integrates four components, namely, polydimethyldiallylammonium chloride, polyferric sulfate solution, sodium percarbonate particles and slag porous particles, into a composite conditioning agent. The material components of different uses are cleverly matched and interacted with each other to effectively integrate the three reaction requirements of positive charge neutralization, sludge floc skeleton and advanced oxidation. While giving full play to their respective advantages, a certain linkage effect is generated, which greatly enhances the dewatering performance of sludge. At the same time, the dosage is small and the efficiency is high. There is no need to use toxic substances such as CPAM that are difficult to degrade, have neurotoxicity or easily cause secondary pollution. The overall environment is more environmentally friendly, efficient and low-cost, and it is suitable for promotion and application. It can be applied to the deep dehydration conditioning of municipal sludge, riverbed sludge and industrial sludge, and has a wide range of applications.

[0023] The sludge treated with the sludge conditioner of the present invention has high calorific value, strong resource utilization, no secondary pollution, and reduces the subsequent disposal cost. According to the subsequent disposal requirements, it can be selected for sanitary landfill or transported to a power plant for incineration and power generation or aerobic fermentation to prepare organic fertilizer. For sanitary landfill, the water content is low, the sludge volume is greatly reduced, the landfill space is saved, and it is not easy to dissolve and seep out, which prevents the sludge from secondary pollution to the land around the landfill. It is used for incineration and power generation in power plants without adding combustion-supporting fuel. When the heavy metal content reaches the fertilizer standard, it can be used for aerobic fermentation to prepare organic fertilizer and bio-organic fertilizer. The moisture content of the mud cake is 50-60%, which is suitable for the water required for aerobic fermentation. It only needs to add a small amount of straw to adjust its air permeability and then add bacterial agent for aerobic fermentation. The obtained fertilizer can be used for greening fertilization and soil improvement. It can achieve stabilization, reduction, harmlessness and resource treatment and disposal of sludge.

[0024] Preferably, potassium monopersulfate composite powder is also included.

[0025] By introducing potassium monopersulfate composite powder, i.e. potassium monopersulfate composite salt, it can not only further enhance the oxidation performance and promote the degradation and dehydration of sludge, but also play a role in disinfection, and it is non-toxic and will not produce harmful substances. Its main components include potassium monopersulfate, potassium hydrogen sulfate and potassium sulfate.

[0026] Preferably, it also includes one or a mixture of lime powder, diatomaceous earth and fly ash.

[0027] Preferably, the invention also comprises a mixture of one or both of cationic guar gum and polyallylamine hydrochloride.

[0028] Through the oxidation and wall breaking effect of potassium monopersulfate composite powder, the skeleton building effect of talcum powder, the electrical neutralization effect of the positively charged groups of polydimethyldiallylammonium chloride on the negatively charged organic colloids in the sludge, and the excellent bridging and coagulation function of the polymer, the colloidal particles are aggregated into large flocs and separated from their suspension, with obvious sludge conditioning effect.

[0029] Preferably, the mass proportions of the components are as follows: 6-8% sodium percarbonate solid particles, 50-65% polyferric sulfate solution, 3-5% polydimethyldiallylammonium chloride, and 25-40% slag.

[0030] Preferably, the polyferric sulfate solution is a liquid with an effective iron content of 11%; and the porous slag particles are 200-300 meshes.

[0031] Preferably, the polydimethyldiallyl ammonium chloride is a dimethyldiallyl ammonium chloride homopolymer having a solid content of 19-21% and a viscosity of 1000-3000 cps.

[0032] Sodium percarbonate solid particles, accounting for 6-8%, have the advantages of being non-toxic, odorless, pollution-free, and slow-release. At the same time, they can also form a Fenton reaction when encountering iron ions in the copolymer, enhancing the oxidizing property and thus achieving stronger oxidation wall breaking. The slag is preferably 200-300 mesh particles, making full use of the porous nature of the particles to form a water passage in the sludge filter press process.

[0033] In order to conveniently and efficiently prepare a sludge dewatering conditioner that can achieve significant sludge volume reduction, cost reduction, and efficiency increase and is environmentally friendly, the present invention also provides a method for preparing a high-efficiency composite sludge dewatering conditioner, comprising the following steps: S1. Mixing polydimethyldiallyl ammonium chloride and polyferric sulfate solution in a weight ratio of 1: (12-20) at a temperature of 50-60° C. to generate a copolymer of polydimethyldiallyl ammonium chloride and polyferric sulfate; S2. The obtained copolymer of polydimethyldiallylammonium chloride and polyferric sulfate is stirred, and the slag porous particles and sodium percarbonate added during the stirring are mixed evenly to obtain a finished sludge dehydration conditioner.

[0034] The copolymer of polydimethyldiallylammonium chloride and polyferric sulfate is mixed and reacted at a weight ratio of 1:15-20 at a temperature of 50-60°C to promote the formation of the copolymer, so that compared with the monomer, under the same effect conditions, the dosage is less and the application range is wider.

[0035] In order to use the sludge dewatering conditioner simply and quickly, and achieve the purpose of significantly reducing the volume and amount of sludge, reducing costs and increasing efficiency, and protecting the environment, the present invention also provides a method for using a high-efficiency composite sludge dewatering conditioner, and the specific steps are as follows: a. adding the sludge dehydration conditioning agent to be treated according to the sludge volume and moisture content, and stirring the reaction; b. After stirring, filter press is performed with a membrane filter press to obtain a dehydrated mud cake.

[0036] Preferably, in the step a, the sludge dehydration conditioner is added according to 15-20% of the absolute dry mass of the sludge.

[0037] Preferably, in step b, the stirring speed is selected to be 80-150 rpm, and the stirring time is 15 minutes.

[0038] The method of the present invention is convenient, fast, and efficient, short in time consumption, high in dehydration rate, and small in sludge increment, and effectively realizes small in sludge increment and substantial reduction in sludge volume and amount.

[0039] The above technical solution of the present invention includes at least the following beneficial effects: (1) The high-efficiency composite sludge dewatering conditioner of the present invention effectively integrates the compression double-layer effect and adsorption and electrical neutralization effect of the copolymer of polydimethyldiallylammonium chloride and polyferric sulfate, and at the same time, with the help of the adhesion bridging, netting and sweeping effects of the polymer chain, the original tiny sludge particles are aggregated into larger particles, thereby improving the sludge settling performance. The slag is an environmental multifunctional material with low cost, huge specific surface area and large porosity, and good physical and chemical stability. It can be used as the floc skeleton of sludge dewatering to maintain the fluid channel, reduce the interfacial tension between the solid and the liquid, and release the water contained in the sludge floc grid. These materials are cleverly matched and complement each other, changing the properties of sludge particles and enhancing the sludge dewatering performance. With the diaphragm plate and frame filter press, the sludge volume reduction is large, and the sludge water content can be reduced to 50-60%. The sludge dewatering performance is strong and the volume reduction is large.

[0040] (2) The present invention has a bactericidal and disinfecting effect, and makes the sludge harmless. By introducing sodium percarbonate, hydrogen peroxide can be continuously produced at room temperature, which reacts with the iron in the copolymer of polydimethyldiallylammonium chloride and polyferric sulfate to generate hydroxyl radicals (-OH). The two substances interact with each other to form a strong oxidizing property, which can not only break the wall to improve the dehydration of the sludge, but also remove reducing substances such as hydrogen sulfide, ammonia, cyanide, methane, methyl mercaptan, etc. in the sludge, and kill bacteria and germs in the sludge to make the sludge harmless and reduce odor.

[0041] (3) The high-efficiency composite sludge dewatering conditioner of the present invention is simple to add, liquid addition, environmentally friendly, low labor intensity, and more widely applicable. It has a good conditioning effect on sludge of different properties. At the same time, the sludge treated by the product of the present invention has a moisture content of less than 60% after dehydration, and has the characteristics of low salt content, high organic matter, and high calorific value. It has strong resource utilization, does not produce secondary pollution, and reduces subsequent disposal costs.

[0042] (4) The present invention has a small dosage, a small sludge increment, and a low treatment cost. It does not require the addition of catalysts, initiators, pH regulators and other reagents. The further enhanced oxidation wall breaking effect of potassium monopersulfate composite powder, the auxiliary enhanced skeleton construction effect of talcum powder, and the positive charge group of polydimethyldiallyl ammonium chloride neutralize the negative charge organic colloid in the sludge and the excellent bridging and coagulation function of the polymer promote the colloidal particles to aggregate into large flocs and separate them from their suspension, and the sludge conditioning effect is obvious. The dosage is small, the sludge increment is controlled at less than 2%, and the treatment cost is low, which is 15-30% lower than the traditional sludge conditioning method. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 The sludge filtration results after sludge conditioning using the dehydrating agents of Example 4 of the present invention and Comparative Example 2 respectively; Figure 2 The sludge filtration results after sludge conditioning using the dehydrating agents of Example 5 of the present invention and Comparative Example 3 respectively; Figure 3 This is a diagram showing the sludge filtration results after sludge conditioning using Example 5 of the present invention. DETAILED DESCRIPTION

[0044] To make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the following will be combined with the appended drawings of the embodiments of the present invention. Figure 1-3 , the technical scheme of the embodiment of the present invention is clearly and completely described. Obviously, the described embodiment is a part of the embodiment of the present invention, not all of the embodiments. Based on the described embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.

[0045] The sludge treated in the following examples and comparative examples is all from a municipal sewage treatment plant in Gansu Province, with a water content of 97.0%. The on-site program-controlled diaphragm plate-frame filter press has a filtration area of ​​200 square meters, and a single batch can process 0.8 tons of dry sludge. In the following examples and comparative examples, 25m 3 The original sludge was subjected to production test, and the absolute dry sludge volume was 0.75 tons.

[0046] Example 1 A highly efficient composite sludge dewatering conditioner, the mass of each component is as follows: 12kg of sodium percarbonate solid particles, 130kg of polyferric sulfate solution, 8kg of polydimethyldiallyl ammonium chloride, and 25kg of slag. The polyferric sulfate solution is a liquid with an effective iron content of 6%, prepared with deionized water as a solvent; the slag porous particles are 300 meshes. Polydimethyldiallyl ammonium chloride is a homopolymer of dimethyldiallyl ammonium chloride with a solid content of 19% and a viscosity of 1000cps.

[0047] And prepared by the following steps: The polydimethyldiallyl ammonium chloride and the polyferric sulfate solution are mixed and reacted at a temperature of 50° C. to generate a copolymer of the polydimethyldiallyl ammonium chloride and the polyferric sulfate; The obtained copolymer of polydimethyldiallylammonium chloride and polyferric sulfate is stirred, and during this process, slag porous particles and sodium percarbonate are added and mixed evenly to obtain a finished sludge dehydration conditioner.

[0048] The process of deep dehydration of sludge using the sludge dehydration conditioner prepared above is as follows: To 25m to be processed 3 112.5 kg of the sludge dehydration conditioner prepared above was added to the sludge, and the mixture was stirred after adding the sludge. The stirring speed was 80 rpm and the stirring time was 15 minutes.

[0049] After conditioning, the sludge enters the diaphragm plate and frame filter press for filtration. The mud inlet pressure is 0.9MPa, the pressing pressure of the secondary pressing is 1.4MPa, and the pressing time is 30min. After the filtration is completed, the mud cake does not stick to the filter cloth, the moisture content of the mud cake is 56.5%, the sludge increase is about 2.0%, the sludge has no obvious odor, and the filtrate is relatively clear.

[0050] Example 2 A highly efficient composite sludge dewatering conditioner, the mass proportion of each component is as follows: 14kg of sodium percarbonate solid particles, 100kg of polyferric sulfate solution, 6kg of polydimethyldiallyl ammonium chloride, and 80kg of slag. The polyferric sulfate solution is a liquid with an effective iron content of 16%; the slag porous particles are 200 mesh. Polydimethyldiallyl ammonium chloride is a homopolymer of dimethyldiallyl ammonium chloride with a solid content of 21% and a viscosity of 3000cps.

[0051] And prepared by the following steps: The polydimethyldiallylammonium chloride and the polyferric sulfate solution are mixed and reacted at a temperature of 60° C. to generate a copolymer of the polydimethyldiallylammonium chloride and the polyferric sulfate; The obtained copolymer of polydimethyldiallylammonium chloride and polyferric sulfate is stirred, and during this process, slag porous particles and sodium percarbonate are added and mixed evenly to obtain a finished sludge dehydration conditioner.

[0052] The process of deep dehydration of sludge using the sludge dehydration conditioner prepared above is as follows: To 25m to be processed 3 150 kg of the sludge dehydration conditioner prepared above was added to the sludge, and the mixture was stirred after adding the sludge. The stirring speed was 150 rpm and the stirring time was 15 minutes.

[0053] After conditioning, the sludge enters the diaphragm plate and frame filter press for filtration. The mud inlet pressure is 1.1MPa, the pressing pressure of the secondary pressing is 1.5MPa, and the pressing time is 30min. After the filtration is completed, the mud cake does not stick to the filter cloth, the moisture content of the mud cake is 54.5%, the sludge increase is about 2.5%, the sludge has no obvious odor, and the filtrate is relatively clear.

[0054] Example 3 A highly efficient composite sludge dewatering conditioner, the mass proportion of each component is as follows: 16kg of sodium percarbonate solid particles, 120kg of polyferric sulfate solution, 10kg of polydimethyldiallyl ammonium chloride, 54kg of slag, and 1kg of lime. The polyferric sulfate solution is a liquid with an effective iron content of 12%; the slag porous particles are 250 mesh. Polydimethyldiallyl ammonium chloride is a homopolymer of dimethyldiallyl ammonium chloride with a solid content of 20% and a viscosity of 2000cps.

[0055] And prepared by the following steps: The polydimethyldiallyl ammonium chloride and the polyferric sulfate solution are mixed and reacted at a temperature of 55° C. to generate a copolymer of the polydimethyldiallyl ammonium chloride and the polyferric sulfate; The obtained copolymer of polydimethyldiallylammonium chloride and polyferric sulfate is stirred, and during this process, slag porous particles, lime and sodium percarbonate are added and mixed evenly to obtain a finished sludge dehydration conditioner.

[0056] The process of deep dehydration of sludge using the sludge dehydration conditioner prepared above is as follows: To 25m to be processed 3 135 kg of the sludge dehydration conditioner prepared above was added to the sludge, and the mixture was stirred after adding the sludge. The stirring speed was selected to be 120 rpm and the stirring time was 15 minutes.

[0057] After conditioning, the sludge enters the diaphragm plate and frame filter press for filtration. The mud inlet pressure is 1.0MPa, the pressing pressure of the secondary pressing is 1.5MPa, and the pressing time is 30min. After the filtration is completed, the mud cake does not stick to the filter cloth, the moisture content of the mud cake is 53.7%, the sludge increase is about 2.0%, the sludge has no obvious odor, and the filtrate is relatively clear.

[0058] Example 4 A highly efficient composite sludge dewatering conditioner, the mass proportion of each component is as follows: 16kg of sodium percarbonate solid particles, 120kg of polyferric sulfate solution, 8kg of polydimethyldiallyl ammonium chloride, 56kg of slag, 0.5kg of potassium monopersulfate composite powder, 1kg of diatomaceous earth, and 1kg of polyallylamine hydrochloride. The polyferric sulfate solution is a liquid with an effective iron content of 11%; the slag porous particles are 200 mesh. Polydimethyldiallyl ammonium chloride is a homopolymer of dimethyldiallyl ammonium chloride with a solid content of 20% and a viscosity of 2000cps.

[0059] And prepared by the following steps: The polydimethyldiallylammonium chloride and the polyferric sulfate solution are mixed and reacted at a temperature of 60° C. to generate a copolymer of the polydimethyldiallylammonium chloride and the polyferric sulfate; The obtained copolymer of polydimethyldiallylammonium chloride and polyferric sulfate is stirred, and during this process, slag porous particles, sodium percarbonate, potassium monopersulfate composite powder, diatomaceous earth and polyallylamine hydrochloride are added and mixed evenly to obtain a finished sludge dehydration conditioner.

[0060] The process of deep dehydration of sludge using the sludge dehydration conditioner prepared above is as follows: To 25m to be processed 3 135 kg of the sludge dehydration conditioner prepared above was added to the sludge, and the mixture was stirred after adding the sludge. The stirring speed was selected to be 140 rpm and the stirring time was 15 minutes.

[0061] After conditioning, the sludge enters the diaphragm plate and frame filter press for filtration. The mud inlet pressure is 1.1MPa, the pressing pressure of the secondary pressing is 1.5MPa, and the pressing time is 30min. After the filtration is completed, the mud cake does not stick to the filter cloth, the moisture content of the mud cake is 52.3%, the sludge increase is about 1.8%, the sludge has no obvious odor, and the filtrate is relatively clear.

[0062] Example 5 A highly efficient composite sludge dewatering conditioner, the mass proportion of each component is as follows: 14kg of sodium percarbonate solid particles, 118kg of polyferric sulfate solution, 8kg of polydimethyldiallyl ammonium chloride, 60kg of slag, 0.5kg of potassium monopersulfate composite powder, and 1kg of cationic guar gum. The polyferric sulfate solution is a liquid with an effective iron content of 11%; the slag porous particles are 200 mesh. Polydimethyldiallyl ammonium chloride is a homopolymer of dimethyldiallyl ammonium chloride with a solid content of 20% and a viscosity of 2000cps.

[0063] And prepared by the following steps: The polydimethyldiallylammonium chloride and the polyferric sulfate solution are mixed and reacted at a temperature of 60° C. to generate a copolymer of the polydimethyldiallylammonium chloride and the polyferric sulfate; The obtained copolymer of polydimethyldiallylammonium chloride and polyferric sulfate is stirred, and during this process, slag porous particles, potassium monopersulfate composite powder, cationic guar gum and sodium percarbonate are added and mixed evenly to obtain a finished sludge dehydration conditioner.

[0064] The process of deep dehydration of sludge using the sludge dehydration conditioner prepared above is as follows: To 25m to be processed 3 130 kg of the sludge dehydration conditioner prepared above was added to the sludge, and the mixture was stirred after adding the sludge. The stirring speed was selected to be 130 rpm and the stirring time was 15 minutes.

[0065] After conditioning, the sludge enters the diaphragm plate and frame filter press for filtration. The mud inlet pressure is 1.0MPa, the pressing pressure of the secondary pressing is 1.4MPa, and the pressing time is 30min. After the filtration is completed, the mud cake does not stick to the filter cloth, the moisture content of the mud cake is 52.6%, the sludge increase is about 1.9%, the sludge has no obvious odor, and the filtrate is relatively clear.

[0066] Comparative Example 1 Use traditional inorganic salt sludge dehydrating agent: "FeCl3+CaO" is used as the dehydrating agent for conditioning, and FeCl3 solution and 15% CaO are added according to 30% of the absolute dry sludge volume.

[0067] (1) To the 25m to be processed 3 Add 225kg FeCl3 (effective iron content 38%) to the sludge, stir while adding, and continue stirring for 10 minutes after adding.

[0068] (2) Add another 112.5 kg of CaO while stirring. Continue stirring for 40 minutes after the addition is completed.

[0069] (3) After conditioning, a program-controlled diaphragm plate and frame filter press is used for filtration. The sludge is fed by a plunger pump with a sludge inlet pressure of 1.0 MPa. The pressing pressure of the secondary pressing is 1.5 MPa and the pressing time is 30 min. After filtration, the mud cake does not stick to the filter cloth, the moisture content of the mud cake is 58.0%, and the sludge increment is about 20%.

[0070] Comparative Example 2 The organic sludge dehydrating agent commonly used in the industry is used: ferric chloride and polyacrylamide are used for conditioning.

[0071] To 25m to be processed 3 Add 1.5kg of polyacrylamide (2kg per ton of absolute dry mud) to the sludge, stir and mix, then add 225kg FeCl3 (effective iron content 38%), stir at 180 rpm for 20 minutes, the mud inlet pressure is 0.9~1.1MPa, the pressing pressure of the secondary pressing is 1.4~1.5MPa, and the pressing time is 30min. After the filtration is completed, the mud cake sticks to the filter cloth obviously, the mud unloading is difficult, the mud cake is elastic, the mud cake moisture content is 67.2%, and the sludge increase is about 5%.

[0072] Comparative Example 3 Compared with Example 4, the only difference is that sodium percarbonate is missing, and the other material components and preparation steps remain unchanged to obtain a finished sludge dehydration conditioner. The same method of use as in Example 4 is used to treat sludge. After the filter press is completed, the mud cake does not stick to the filter cloth, the moisture content of the mud cake is 58.4%, the sludge increment is about 3.6%, the sludge has a slight odor, and the filtrate is slightly turbid.

[0073] Comparative Example 4 Compared with Example 5, the only difference is the lack of slag porous particles, and the other material components and preparation steps remain unchanged to obtain a finished sludge dehydration conditioner. The same method of use as in Example 4 is used to treat sludge. After the filter press is completed, the mud cake sticks to the filter cloth, the moisture content of the mud cake is 63.9%, the sludge increment is about 6.6%, the sludge and the filtrate have a strong irritating taste, and the filtrate is turbid.

[0074] The sludge dehydration conditioners prepared in Examples 1-5 and Comparative Examples 1-4 were subjected to appearance inspection and sludge treatment tests. The moisture content of the mud cake, the sludge increment, the pH value of the filtrate and other indicators were tested. The degree of resource utilization, labor intensity, working environment and the operating costs of the sample products during the test were comprehensively evaluated. The sludge dehydration conditioners were subjected to appearance inspection and sludge treatment tests. The sludge dehydration conditioners were subjected to ... 3 Taking sludge as an example, the statistics are summarized and the results are shown in Tables 1 and 2 below.

[0075] Table 1

[0076] Table 2

[0077] As shown in Table 1 and Table 2 above, the sludge dehydration conditioner obtained in Examples 1-5 has excellent sludge dehydration performance, which can not only reduce the sludge moisture content to below 60%, but also control the sludge moisture content within 56.5%, and control the sludge increment to below 2.5%. The mud cake has low salt content, low moisture content, no pathogenic bacteria, no obvious odor, and the filtrate is relatively clear, which is suitable for resource applications such as incineration power generation and manufacturing of bio-organic fertilizer. It is also environmentally friendly, has low labor intensity, is environmentally friendly, and can save costs.

[0078] Comparative Example 1 uses a traditional inorganic salt sludge dehydrating agent (taking "FeCl3+CaO" as an example). Compared with the product obtained in Example 4, although it can reduce the sludge moisture content to below 60%, the sludge increment is more than 20%, and the labor intensity is high when adding the agent, which causes serious corrosion to the equipment. The obtained mud cake has a high salt content, which increases the transportation cost and disposal cost, and is not conducive to resource utilization and disposal methods such as incineration power generation and manufacturing organic fertilizer. Comparative Example 2 uses polyacrylamide plus ferric chloride sludge dehydrating agent. Although the sludge increment is general, it cannot reduce the sludge moisture content to below 60%, and the mud cake is seriously sticky, making it difficult to unload the mud, blocking the filter cloth, and the dehydration effect is poor, and the cost is high. Figure 1 As shown, Figure 1The small picture on the left is the sludge sample after being treated with the product of Example 4, and the small picture on the right is the sludge sample after being treated with the product of Comparative Example 2. It can be seen that the sludge treated with the product of Example 4 is very dry and has a low moisture content, while the moisture content of the sludge treated with the product of Comparative Example 2 is still relatively high, and the dehydration effect is not good.

[0079] It can be seen from the experimental results of Comparative Examples 3 and 4 that the sludge dehydration conditioner obtained by lacking sodium percarbonate or using CaO instead of slag porous particles has a significantly lower dehydration effect than the products obtained in Examples 4 and 5. The moisture content of the mud cake in Comparative Example 4 even reaches more than 60%, and the sludge increment becomes larger, the sludge and filtrate have a strong irritating taste, and the filtrate is turbid. Figure 1 As shown, Figure 1 The small picture on the left is the sludge sample after being treated by the product of Example 4, and the small picture on the right is the sludge sample after being treated by the product of Comparative Example 2. It can be seen that the sludge treated by the product of Example 4 is relatively dry and has a significantly lower moisture content. Figure 2 As shown, Figure 1 The small picture on the left is the sludge sample after being treated with the product of Comparative Example 3, and the small picture on the right is the sludge sample after being treated with the product of Example 5; and Figure 3 The figure shows an enlarged picture of the sludge sample after being treated with the product of Example 5. It can be seen that the sludge treated with the product of Example 5 is drier than the sludge treated with the product of Comparative Example 3, and has a significantly lower water content. Although the dehydration rate of the sludge treated with the product of Comparative Example 3 is also lower than 60%, the dehydrated sludge has a slight odor and the filtrate is slightly turbid.

[0080] The components in the present invention coordinate and promote each other, and finally achieve high dehydration efficiency while keeping sludge increment low, and have no toxic substances, are environmentally friendly and have the lowest cost, and are suitable for industrial promotion and application.

[0081] The above are preferred embodiments of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.

Claims

1. A highly efficient composite sludge dewatering conditioner, characterized in that: It includes polydimethyldiallylammonium chloride, polyferric sulfate solution, sodium percarbonate particles and porous slag particles; The polyferric sulfate solution is a liquid having an effective iron content of 6 to 16%; The polydimethyldiallyl ammonium chloride and the polyferric sulfate solution are mixed and reacted in a weight ratio of 1:(12-20) under heating conditions to obtain a copolymer of polydimethyldiallyl ammonium chloride and polyferric sulfate.

2. The high-efficiency composite sludge dewatering conditioner according to claim 1, characterized in that: Also included is potassium monopersulfate composite powder.

3. The high-efficiency composite sludge dewatering conditioner according to claim 1, characterized in that: It also includes one or a mixture of lime powder, diatomaceous earth and fly ash.

4. The high-efficiency composite sludge dewatering conditioner according to claim 1, characterized in that: Also included are a mixture of one or both of cationic guar gum and polyallylamine hydrochloride.

5. The high-efficiency composite sludge dewatering conditioner according to claim 1, characterized in that: The mass proportion of each component is as follows: Sodium percarbonate solid particles 6~8%, polyferric sulfate solution 50~65%, polydimethyldiallylammonium chloride 3~5%, slag 25~40%.

6. The high-efficiency composite sludge dewatering conditioner according to claim 1, characterized in that: The polyferric sulfate solution is a liquid with an effective iron content of 11%; the porous slag particles are 200-300 meshes.

7. The method according to claim 1, characterized in that: The polydimethyldiallyl ammonium chloride is a dimethyldiallyl ammonium chloride homopolymer with a solid content of 19-21% and a viscosity of 1000-3000 cps.

8. The method for preparing a high-efficiency composite sludge dewatering conditioner according to any one of claims 1 to 7, characterized in that: The following steps are included: S1. Mixing polydimethyldiallyl ammonium chloride and polyferric sulfate solution in a weight ratio of 1: (12-20) at a temperature of 50-60° C. to generate a copolymer of polydimethyldiallyl ammonium chloride and polyferric sulfate; S2. The obtained copolymer of polydimethyldiallylammonium chloride and polyferric sulfate is stirred, and the slag porous particles and sodium percarbonate added during the stirring are mixed evenly to obtain a finished sludge dehydration conditioner.

9. The method for using the high-efficiency composite sludge dewatering conditioner according to any one of claims 1 to 7, characterized in that: The specific steps are as follows: a. adding the sludge dehydration conditioning agent to be treated according to the sludge volume and moisture content, and stirring the reaction; b. After stirring, filter press is performed with a membrane filter press to obtain a dehydrated mud cake.

10. The method for using a high-efficiency composite sludge dewatering conditioner according to claim 9, characterized in that: In the step a, the sludge dehydration conditioning agent is added according to 15-20% of the absolute dry mass of the sludge; in the step b, the stirring speed is selected to be 80-150 rpm, and the stirring time is 15 minutes.

Citation Information

Patent Citations

  • Compound conditioning and deep dewatering method of sludge

    CN104649533A

  • Method for improving municipal sludge dewatering performance

    CN105502882A

  • Sludge dewatering composite conditioning agent and sludge dewatering method

    CN106746482A

  • Efficient dewatering agent for sewage sludge as well as preparation method and application of efficient dewatering agent

    CN108083613A

  • Novel sludge dewatering agent

    CN108409104A